An exegetical study of imprecatory Psalms in the Old Testament - Simango, Daniel (North-West University, 2011)
This thesis is an attempt to read the imprecatory psalms in the Old Testament more effectively. In the introduction, the current research of the imprecatory psalms is surveyed and three problems are identified. First of all, there seems to be no consensus among scholars with regards to the exact number of imprecatory psalms. The reason for this is that there are no defined criteria for identifying these psalms. Little work has been done to rectify the situation, possibly because the search for such criteria has been arbitrary and subjective. It is probably unnecessary for scholars to sing in unison with regards to the exact number of imprecatory psalms. Therefore, rather than searching for some illusive criteria, this study focuses on the content of these psalms in order to enrich our understanding of imprecation in the Psalms. Secondly, there is a wide range of views regarding the basis of imprecatory psalms. There is no consensus among scholars and many of the proposed solutions are unsatisfactory. Therefore, this study focuses on each imprecatory psalm to establish the basis of imprecation from the text itself and then seeks to clarify the “ethical problem” in the light of the New Testament. Thirdly, some scholars seem to have ignored the historical context of the imprecatory psalms. Therefore, this study is an attempt to read the imprecatory psalms in their total context (i.e historical, life-setting and canonical) before application is made to the modern context. Thus, the above research problems have provided motivation for this thoroughly text-based and text oriented exegetical study of a representative selection of the imprecatory psalms in order to grasp more accurately the content, context and message of these psalms. In order to ensure the thoroughness of this study, the reading strategy utilized involves a three-dimensional approach, namely an intra-textual reading, an extra-textual reading and an inter-textual reading of each of the representative imprecatory psalms. From the perspective of intra-textual reading, the literary structure, morphological, poetical, semantic and rhetorical features of each of the representative imprecatory psalms are investigated. Following this, the extra-textual dimensions of each of the representative imprecatory psalms are discussed in order to scrutinize the socio-historical context of imprecatory psalms. The aspect of the inter-textual relationships of each of the representative imprecatory psalms is also examined in order to understand imprecatory psalms in their broader canonical context. For the purpose of this study, five imprecatory psalms, namely Psalms 35, 69, 83, 109 and 137, have been selected, based on the fact that they are commonly classified by scholars as imprecatory psalms. Psalms 35, 69, 83, 109 and 137 are multi-dimensionally read in the main body of the thesis (chapters 2-6, one chapter for each imprecatory psalm), based on the suggested three-dimensional reading, namely the intra-textual reading, the extra-textual reading and the inter-textual reading. The thesis concludes by comparing the content, context and theological emphasis of the selected imprecatory psalms. It synthesizes all the study outcomes, the overall messages and theological implications of the selected imprecatory psalms and gives clarity on the “ethical problem.” Finally, some suggestions for future research on imprecatory psalms are offered.
free